Pneumatic lithotripsy versus laser lithotripsy in the endoscopic treatment of ureteral calculi (Bangladesh Medical Journal, 2025)
Ureteroscopy (URS) is a precise, minimally invasive surgical procedure that have emerged as the standard approach for treating large ureteral stones in many medical facilities, owing to their comparatively low complication rates and high success in achieving stone-free outcomes. In the context of ureteroscopic lithotripsy, various types of lithotripters are available, including electrohydraulic, ultrasonic, pneumatic, and laser options. Among these, laser lithotripsy (LL) and pneumatic lithotripsy (PL) are the most commonly utilized methods. The aim of this cross-sectional analytical study was carried out to compare the outcome of LL and PL in the management of ureteric calculi. Over the course of a year (from November 2022 to October 2023), this study was conducted among 96 patients with ureteral calculi in the Department of Urology at Bangabandhu Ssheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh. Following the acquisition of both verbal and written consent from every patient, participants were enrolled in this study. The patients were categorized into two groups: Group A and Group B. Those who underwent procedure LL were placed in Group A, whereas those who received PL were assigned to Group B. A questionnaire was developed to gather data. Each patient was interviewed regarding their medical history and clinical characteristics, which included outcome variables such as the size of the stone, its location, the stone clearance rate, the duration of the procedure, the necessity for the Double J (DJ) method, the length of hospital stay, complications, the frequency of stone retrieval instrument usage, the rate of proximal fragment migration, and the requirement for Extracorporeal Shock Wave Lithotripsy (ESWL). The outcomes of the two procedures were compared in terms of stone clearance rate, duration of the procedure, requirement for DJ, length of hospital stay, complications, frequency of stone retrieval instrument usage, rate of proximal fragment migration, and necessity for ESWL. The data were analyzed using the statistical package for social sciences (SPSS) version 23.0. The mean age of participants in the LL group was 38.94 ± 9.47 years (range: 21-55), while in the PL group it was 36.46 ± 8.72 years (range: 23-50), with no significant difference (p>0.05). There was a predominance of males in both groups (p>0.05). The LL group had more right-sided stones while the PL group had more bilateral instances (p>0.05). Laser lithotripsy demonstrated less stone migration and DJ stenting, a higher stone-free rate, and shorter operative times compared to pneumatic lithotripsy. Both modalities were effective and safe for proximal ureteric calculus management. The mean size of stones was almost similar in both the LL and PL groups, with no significant difference observed. The stone size measured 10.37 ± 2.45 (ranging from 7.25 to 19.0) mm in the LL group, while it was 9.98 ± 2.26 (ranging from 7 to 17) mm in the PL group. The operative time was significantly short in the LL group compared to the PL group, recorded at 43.35 ± 3.86 minutes versus 55.08 ± 3.79 minutes; p